Diagnóstico de salud bucodental y factores de riesgo en los Centros Educativos Primarios: González Suarez, Adolfo Valarezo y María Dominga Guaya Sinche de la parroquia Chuquiribamba del cantón Loja en el año 2013 - Guamán Camacho, Magaly Judith (2013)
Oral hygiene diseases appear of correlation of many risk factors present in the individual; the pathologies affect different age’s groups. For this, it was realized the present research: quantitative, descriptive and transverse; whose end was realized the diagnosis of oral hygiene health in 150 students of primary schools: “González Suarez”, “Adolfo Valarezo” y “María Dominga Guaya Sinche” in Chuquiribamba parish, in Loja canton, to identify the risk factors predisposing to oral hygiene diseases, and to determine the prevalence of these pathologies; trough the realization of diagnostics oral and the application of survey about oral hygiene and risk factors to each student. The pathologies found were: caries 98%, gingival inflammation 83%, gingival bleeding 8% and mild fluorosis 4%. In the molar radio: 80% in the straight terminal plane and 55% class I with crowding. In addition, the 12% presented bite bis a bis and 16% premature loss of deciduous dentition. Within of risks factors finding: 37% brushing teeth once a day and 8% don not brush teeth, the students eat cariogenic foods more than 3 times a day the 21% and 66% visit to dentist once a year.